Optimization of tokamak disruption scenarios - Bergström, Hannes; Halldestam, Peter (My University, 2022)
Research in the field of fusion science has been propelled by its potential to alleviate humanity’s reliance on fossil fuels. One of today’s most promising approaches to generating thermonuclear fusion energy uses magnetic confinement of hydrogen fuel in the plasma state. The tokamak concept, which has achieved the best fusion performance so far, is used in the three reactor-scale devices (ITER, SPARC and STEP) currently being constructed — they aim to achieve a positive energy balance, thereby demonstrating the scientific feasibility of magnetic confinement fusion energy. A major open issue threatening the success of these tokamaks is plasma disruption. In these off-normal events the plasma loses most of its thermal energy on a millisecond timescale, exposing the device to excessive mechanical stress and heat loads. In addition, in the high-current devices currently under construction, one of the most important related problems is posed by currents carried by electrons accelerated to relativistic energies, called runaway electrons. If these were to strike the inner wall unmitigated, it may cause potentially irreversible damage to the device. The methods proposed to mitigate these dangerous effects of disruptions, such as massive material injection, are characterized by a large number of parameters, such as when to inject material, in which form and composition. This poses an optimization problem that involves a potentially high-dimensional parameter space and a large number of disruption simulations. In this work, we have developed an optimization framework that we apply to numerical disruption simulations of plasmas representative of ITER, aiming to find initial conditions for which large runaway beams and excessive wall loads can be avoided. We assess the performance of mitigation when inducing the disruption by massive material injection of neon and deuterium gas. The optimization metric takes into account the maximum runaway current, the transported fraction of the heat loss — affecting heat loads — and the temporal evolution of the ohmic plasma current — determining the forces acting on the device.
Keywords: fusion plasma; disruption mitigation; runaway electrons; Powell’s method; Bayesian optimization